Pyrrolidine dithiocarbamate attenuates paraquat-induced acute pulmonary poisoning in vivo via transforming growth factor β1 and nuclear factor κB pathway interaction. (December 2016) - Huang, M; Lou, D; Li, H-H; Cai, Q; Wang, Y-P; Yang, H-F
Paraquat (PQ) exposure could cause pulmonary fibrosis. The aim of this study was to investigate the protective effect of pyrrolidine dithiocarbamate (PDTC) in an acute PQ poison model. One hundred and forty-four Sprague Dawley rats were equally divided into three experimental groups: control group, PQ group, and PQ + PDTC group. At days 1, 3, 7, 14, 28, and 56 of treatment, the serum levels of transforming growth factor β1 (TGF-β1), the levels of hydroxyproline, the protein expression of nuclear factor κB (NF-κB) pathway, and histopathological change in lung tissue were assessed. The survival rate of rats treated with PQ + PDTC was increased compared with that of rats treated only with PQ ( p < 0.05), and the occurrence of pathological changes was dramatically attenuated in the PQ + PDTC group. The serum levels of TGF-β1 and the hydroxyproline levels in the PQ group were significantly increased in a time-dependent manner compared with those in the control and PQ + PDTC groups on days 7, 14, 28, and 56 ( p < 0.05). Additionally, the protein levels of NF-κB proteins p65, inhibitor of κB (IκB) kinase (IKKβ, and IκB-α were significantly downregulated in the PQ + PDTC group as determined by array analysis. The present findings suggest that overexpression of TGF-β1 may play an important role in PQ-induced lung injury and that PDTC, a strong NF-κB inhibitor, can rescue PQ-induced pulmonary fibrosis by influencing the protein expression of NF-κB pathway.